The Functions of Theology to Christian Tradition - Ghasem Kakaie; Ashkan Bahrani (Comparative Theology, 2013)
The term Theology has various definitions and meanings in the Christian tradition. In this article, after discussing these definitions and meanings we have tried to illuminate the extended functions of theology in Christianity and we have also explained the meaning of this term which has been entered to our literature by means of translation from European languages into Persian. In this connection, the history of the term, "theology", is discussed rapidly and then some main branches of theology explained according to its functions. Finally, we have concentrated on some equivalents of "theology" in Persian language.